IDENTIFIKASI FAKTOR-FAKTOR PROFESIONALISME MANAJER PROYEK PADA PROYEK KONSTRUKSI - Diah Parami Dewi, A. A. (Jurnal Ilmiah Teknik Sipil, 2012)
In construction project activities, many human resources are involved. The complexity of the project requires an ability of a project manager to manage it in a good way. Project manager professionalism is one of the keys to the project success. It means that as an individual, each team member should have a reliable professionalism to their constructed project. Based on the literature, it can be identified the factors of project manager professionalism in construction project that includes: planning, organizing, staffing, coordinating, leadership, controlling, development and improvement, directing, self management and policy making.
Keywords: Professionalism, Project Manager, Construction Project